Phytostilbenes as agrochemicals: biosynthesis, bioactivity, metabolic engineering and biotechnology. Issue 7 (22nd December 2020) - Jeandet, Philippe; Vannozzi, Alessandro; Sobarzo-Sánchez, Eduardo; Uddin, Md. Sahab; Bru, Roque; Martínez-Márquez, Ascension; Clément, Christophe; Cordelier, Sylvain; Manayi, Azadeh; Nabavi, Seyed Fazel; Rasekhian, Mahsa; El-Saber Batiha, Gaber; et al.
Abstract : Although constituting a limited chemical family, phytostilbenes represent an emblematic group of molecules among natural compounds. Abstract : Covering: 1976 to 2020. Although constituting a limited chemical family, phytostilbenes represent an emblematic group of molecules among natural compounds. Ever since their discovery as antifungal compounds in plants and their ascribed role in human health and disease, phytostilbenes have never ceased to arouse interest for researchers, leading to a huge development of the literature in this field. Owing to this, the number of references to this class of compounds has reached the tens of thousands. The objective of this article is thus to offer an overview of the different aspects of these compounds through a large bibliography analysis of more than 500 articles. All the aspects regarding phytostilbenes will be covered including their chemistry and biochemistry, regulation of their biosynthesis, biological activities in plants, molecular engineering of stilbene pathways in plants and microbes as well as their biotechnological production by plant cell systems.